Regional Language Studies. Newfoundland, Number 23 (29 October 2012) - Clarke, Sandra; De Decker, Paul; Kirwin, William J., 1925- (William James); Power, Suzanne; Story, G. M. (George Morley), 1927-1994; Van Herk, Gerard; Webb, Jeff A. (Jeffrey Allison), 1962- (Memorial University of Newfoundland. Department of English Language and Literature, 2012)
The view from the sea : Newfoundland place-naming / George Story -- The background of dialect questionnaires in English Department research : an internal report / William J. Kirwin -- Reflections on fieldwork with Dr. John Widdowson / Suzanne Power -- Nine days talk : anthropological evidence in linguistic field notes / Jeff A. Webb -- Rethinking our social labelling of Newfoundland speech features / Gerard Van Herk -- Coffee and change : organizational identity and phonological variation in St. John's / Paul De Decker -- Update on the activities of the English Language Research Centre / Suzanne Power, Sandra Clarke -- Report on Newfoundland and Labrador English research in the Department of Linguistics / Suzanne Power -- Bibliography / Sandra Clarke, Suzanne Power.